PENGEMBANGAN MARKA MOLEKULAR UNTUK KARAKTERISASI VARIETAS ANGGREK TANAH UNGGUL (SPATHOGLOTTIS) HASIL POLIPLOIDISASI DENGAN KOLKISIN - Setiawan, Agus; Shochicha, Anahtadiya Nurfa; Cahya Pramana, Abrory Agus; Restiyanti, Restiyanti; Daryono, Budi Setiadi (Program Kreativitas Mahasiswa - Penelitian, 2013)
Characterization of Spathoglottis has not been observed yet especially in determination of genetic relationship and identification of colchisine-induced polyploid orchid. The aim of this research was to study about characterization of fingerprinting molecular mark in DNA Barcode profiling of Polyploid Anggrek Tanah (Spatholgottis sp.) and fenetic relationship of polyploid orchid with superior hybrid soil orchid (Spatholgottis sp.). The method of this research is collecting the orchid, germinating orchid seed, colchisine-induced PLB orchid, making simply buffer DNA isolation, genome DNA isolation, quantitative test of genome DNA, qualitative test of genome DNA, liquidity DNA genom, liquidity RAPD primer, PCR Random Amplified Polimorphism DNA (RAPD) of Orchid DNA, electrophoresis of PCR-RAPD, polymorphism RAPD , Dendogram RAPD analysis, dan creating Orchid DNA barcode. Based on the result known that RAPD molecular method could be used in detection of polyploid Spathoglottis sp. with OPAW11 primer. Electroforegram could be made as DNA bar-coding for Spathoglottis sp. that also could be used to to trace the origin orchids from Indonesia.Keywords: Spathoglottis, RAPD, bar-code DNA, colchisine